Role of cross currency swap markets in funding and investment decisions - Thomas J. Brophy; Niko Herrala; Raquel Jurado; Irene Katsalirou; Léa Le Quéau; Christian Lizarazo; Seamus O'Donnell (European Central Bank (ECB), 2019)
A US dollar funding premium in the EUR/USD cross currency swap market has been in existence since 2008. Whilst there are many reasons behind this dislocation, since 2014 the divergence in monetary policy between the euro area and the United States has played a growing role. This paper aims at exploring and gaining more insight into the role the Eurosystem's Expanded Asset purchase Programme (APP) has had in guiding investment and funding decisions and its influence on the cross currency basis. The downward pressure on yields, exerted by the APP, has made euro assets less attractive and has led investors to search for yield abroad. At the same time, the decline in yields and tighter credit spreads have attracted US corporate issuers to the euro market in search of cheaper funding costs. These cross-border flows from issuers and investors have played a strong role in driving the US dollar funding premium. The purpose of this study is to gauge whether these changing trends in cross-border flows have implications for the implementation of the Eurosystem's APP. Beyond the structural increase in the US dollar funding premium described above, a cyclical component has led to an amplification of the premium over balance sheet reporting dates, due to new bank regulations. This paper also analyses the behaviour of euro area banks in cross currency swap markets over balance sheet reporting dates, using the money market statistical reporting (MMSR) dataset in order to discern whether the increase in the US dollar funding premium at these specific points in time has an adverse impact on the transmission of monetary policy.
Keywords: D53; E52; G11; G15; G18; 330; cross currency basis swap; US dollar funding premium; monetary policy divergence; cross-border investment and funding flows; balance sheet reporting dates; balance sheet constraints